2016
DOI: 10.5530/ijper.50.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Learning Style Preferences of Undergraduate Pharmacy Students in a Malaysian Public University

Abstract: Objectives:To compare the learning style preferences among pharmacy students at different stages of academic course and to determine the demographic variables that significantly influence the learning style preferences of these students. Methods: A 24-item self-report survey instrument, including the validated Pharmacists' Inventory of Learning Styles (PILS), was administered to all year 1 to year 4 pharmacy students at Universiti Teknologi MARA, Malaysia. Data (e.g. demographic variables, learning style prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The present study found that the predominant learning style in our student population is consistent with the learning styles of pharmacists and pharmacy students reported in the literature [ 43 , 44 , 47 , 61 , 64 – 66 ]. The learning styles primarily reported with the pharmacy profession are assimilator and converger.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present study found that the predominant learning style in our student population is consistent with the learning styles of pharmacists and pharmacy students reported in the literature [ 43 , 44 , 47 , 61 , 64 – 66 ]. The learning styles primarily reported with the pharmacy profession are assimilator and converger.…”
Section: Discussionsupporting
confidence: 90%
“…Second, gender variation in learning styles could have affected their perceptions about the time. Although some studies have reported more men being diverger and women have an assimilator learning style, others did not find such differences [ 44 , 61 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…POPULATION After conducting a sample size calculation, an estimated sample size of 385 respondents was determined with a confidence level of 95% and a 5% margin of error. The sample size was calculated using Raosoft, an online sample size calculation software that has also been used in previous studies (Ahmat et al, 2018;Saadatian et al, 2012). A purposive sampling technique was used in this study, as respondents with certain characteristics (i.e., inclusion criteria) were included in the sample because of their usefulness for the purpose of the study (Taherdoost, 2016).…”
Section: Customers' Attitudes As a Mediating Variable Between Perceiv...mentioning
confidence: 99%
“…The four years of B.Pharm is commonly considered to be a tough program as students are required to study all aspects of pharmaceutical sciences. John et al claim that the extensive range of subjects addressed and the constrained amount of class time may lessen the effectiveness of the teaching-learning relationship (4). Consequently, the learning methods used may have an effect on the effectiveness of the instruction given to students (5).…”
Section: Introductionmentioning
confidence: 99%